Physiotherapists’ perceptions of their professional work readiness after graduation - Suits, Maria; Kangasniemi, Mari; Kommusaar, Janne; Tamm, Anna-Liisa (United Kingdom, 2026)
Purpose
To ensure high-quality, human-centered healthcare, we need competent, skilled, and motivated specialists. Given the constant evolution of physiotherapy, continuous professional development for physiotherapists is essential. Estonia’s Tartu Health Care College has been training physiotherapists (European Qualifications Framework Level 6) for over 20 years with curriculum updates every 5 years. The aim of this study was to describe physiotherapists’ perceptions of their professional work readiness following graduation, generating insights to inform future curriculum development and support evolving professional demands.
Methods
We conducted thematic content analysis (based on the occupational qualification standard) on semi-structured interviews with 11 physiotherapists with up to 2 years’ professional experience.
Results
Physiotherapists described themselves as confident in performing physiotherapeutic assessments and interventions, particularly for chronic conditions, including counselling patients and their support networks. However, challenges were noted in handling complex cases and understanding roles within multidisciplinary teams. Effective communication with patients and colleagues was seen as essential; supportive teams increased confidence. Ethical behaviour was seen as intuitive, though some participants faced unethical behaviour from patients. Challenges in conciseness and specificity of documentation were reported.
Conclusion
Ongoing training is needed to address physiotherapists’ challenges with concise documentation, role clarity in multidisciplinary teams, managing acute or unfamiliar conditions, and managing ethical issues.